(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2025)
Religious Pluralism, A Value of Human Rights in the 21st Century.This article explores significant aspects of religious pluralism at both the global and European levels. It is crucial to understand the involvement of states in recognizing various religious denominations and the corresponding legal frameworks established to ensure equality. This reality is also evident in international relations, particularly within the United Nations, where there is a growing number of initiatives committed to promoting interreligious dialogue. Today, religion constitutes not only a diplomatic or educational dimension but also a social one. The European Union plays a fundamental role in this context, as its policies guarantee the practice of different religions, as enshrined in the Charter of Fundamental Rights and in treaties.